Aportes vs. expectativas de género: dilemas para la educación superior y la industria minera (Polis (Santiago), 2025)
In 2022, female participation in STEM areas in Latin America and the Caribbean grew by 35%. However, this encouraging growth does not yet reflect a significant transformation in mining culture, given the gender dilemmas faced by women in this industry. The objective of this study is to analyze the tension between the contributions made by women vs. the expectations projected on them. The research was carried out from a gender perspective and its configuration in the STEM area. To do this, interviews were conducted: 12 individual interviews with female mining workers and 14 group interviews with technical and university level students. 39 women and 25 men from careers oriented to the sector participated. The results show coincidences among the interviewees, regarding the fact that women are aware that they contribute with communication skills, planning, leadership and responsibility in the sector, but at the same time they face high expectations to achieve notable performances in higher education and in the industry, because the male model of productivity that prevails in the sector operates in "favor of men" and not women.
Keywords: STEM; mining culture; gender; higher education.